Marine Insects - Springer Springer, Monika (2008)
Although insects are one of the most diverse groups of organisms on earth, relatively few species are found associated with marine habitats. The majority of these marine species live in intertidal or coastal habitats and most of them belong to the orders Hemiptera, Diptera, and Coleoptera. Little is known about the marine insects of Central America and no survey of marine insect species has been carried out for Costa Rica. Therefore, this chapter presents a short discussion on each insect order with marine species that are most likely to occur in the area. Nearly nothing is known for the Caribbean coast of Costa Rica. For the Pacific coast a species list is presented that includes one marine species of Collembola, and eight species from four families from the order Hemiptera. This last one is also the only order with truly pelagic insects, the sea skaters Halobates (Gerridae), able to permanently colonize the open ocean.